Adaptation and psychometric evaluation of a scale to measure oral pre‐exposure prophylaxis‐related stigma among key and vulnerable populations in Kenya. (12th July 2022) - Atkins, Kaitlyn; Kan, Lena; Musau, Abednego; Reed, Jason; Were, Daniel; Mohan, Diwakar
Abstract: Introduction: As oral pre‐exposure prophylaxis (PrEP) services scale up throughout sub‐Saharan Africa (SSA), clients continue to face challenges with sustained PrEP use. PrEP‐related stigma has been shown to influence engagement throughout the HIV PrEP care continuum throughout SSA. Validated quantitative measures of PrEP‐related stigma in SSA are of critical importance to better understand its impacts at each stage of the HIV PrEP care continuum. This study aimed to psychometrically evaluate a PrEP‐related stigma scale for use among key and vulnerable populations in the context of a Kenya national PrEP programme. Methods: As part of a larger prospective cohort study nested within Kenya's Jilinde programme, this study used baseline data collected from 1135 participants between September 2018 and April 2020. We used exploratory factor analysis to evaluate the factor structure of a PrEP‐related stigma scale. We also assessed convergent construct validity of the PrEP‐Related Stigma Scale by testing for expected correlations with depression and uptake of HIV services. Finally, we examined the relationship between PrEP‐related stigma and key demographic, psychosocial and behavioural characteristics. Results: We identified four dimensions of PrEP‐related stigma: (1) interpersonal stigma, (2) PrEP norms, (3) negative self‐image and (4) disclosure concerns. The scale demonstrated strong internal consistency (α = 0.84), was positively correlated with depressive symptoms and negatively correlated with uptake of HIV services. Multivariable regression analysis demonstrated associations between PrEP‐related stigma and sex worker identity. Conclusions: The adapted and validated PrEP‐Related Stigma Scale can enable programmes to quantify how PrEP‐related stigma and its dimensions may differentially impact outcomes on the HIV PrEP care continuum, evaluate stigma interventions and tailor programmes accordingly. Opportunities exist to validate the scale in other populations and explore further dimensions of PrEP‐related stigma.